1998
DOI: 10.1038/sj.jhh.1000663
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure changes at the Dead Sea (a low altitude area)

Abstract: The Dead Sea (barometric pressure: 800 mm Hg) is an important balneotherapeutic centre for chronic dermatologic and arthritic diseases. In the past, hypertensive patients have complained sporadically of weakness and dizziness during a stay in the Dead Sea. It was therefore recommended that hypertensives do not stay at these health centres. The aim of our study was to investigate the changes in blood pressure (BP) parameters of 72 hypertensive and normotensive osteoarthritic and rheumatoid arthritic elderly pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Confirming these conclusions, Paran 16 published later on a study in which blood pressure changes were compared in 72 hypertensive and normotensive patients staying in Beer Sheva (barometric pressure 745 mmHg) and at the Dead Sea (barometric pressure 800 mmHg). The sojourn at the Dead Sea showed an average decrease of 17 mmHg, a change that diminished slightly after 10 days stay at the Dead Sea.…”
Section: Hypertension At the Dead Seamentioning
confidence: 86%
“…Confirming these conclusions, Paran 16 published later on a study in which blood pressure changes were compared in 72 hypertensive and normotensive patients staying in Beer Sheva (barometric pressure 745 mmHg) and at the Dead Sea (barometric pressure 800 mmHg). The sojourn at the Dead Sea showed an average decrease of 17 mmHg, a change that diminished slightly after 10 days stay at the Dead Sea.…”
Section: Hypertension At the Dead Seamentioning
confidence: 86%
“…[ 25 ] In a study conducted in 1998, Paran et al . [ 26 ] applied BT to two groups of OA patients, one with HT and the other who were normotensive for a 2-week period in thermomineral water. They recorded a significant reduction in systolic and diastolic blood pressures in the normotensive group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, randomised controlled studies on clinical effects (Schuh 1993;de Andrade et al 2008;Harari et al 2007;Hodak et al 2003;Wolf et al 2003b;Cohen et al 2005;Autio et al 2002) and relevant factors (Cohen et al 2008;Uosif et al 2008;Kovlen et al 2007;Nissen et al 1998) are available within this area. For treatment in specific climatic regions, scientific studies have shown beneficial effects in various health conditions (Kragballe et al 1996;Gutenbrunner et al 2007;Sukenik et al 1990aSukenik et al , 1990bSukenik et al , 1994Sukenik et al , 1995Paran et al 1998;Sukenik 1998;Buskila et al 2001;Neumann et al 2001) Use of other therapeutic factors A description of the use of other therapeutic factors is beyond the framework of this paper. However, they are well known and are described in the textbooks of the fields concerned.…”
Section: Use Of Climatic Factorsmentioning
confidence: 96%